Role of Rare-Earth (Eu, Dy And Yb) substitution on determining the structural, thermal and superconducting properties of BSCCO superconductor prepared via coprecipitation method / Siti Hawa Jamil - Jamil, Siti Hawa (Institute of Graduate Studies, UiTM, 2016)
In this study, the Bi₁.₆Pb₀.₄Sr₂Ca₂₋ₓREₓCu₃Oᵧ (RE = Eu, Dy and Yb) where x= 0.000, 0.025, 0.050, 0.100 and 0.200 which were synthesised through the coprecipitation (COP) method was successfully prepared. The phase purity and structural properties were performed by X-ray Diffractometer (XRD), Field-Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-ray Spectroscopy (EDX). Meanwhile, the powders at each stage of the coprecipitated powder, precalcined and calcined products were characterized by Thermogravimetric Analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR). Furthermore, the resistivity and critical current density were measured by using the four-point probe method. The Bi-2223 superconductor induced the additional Bi-2212 phase with increasing RE concentration. The crystallographic structures of the samples were slightly changed from tetragonal to orthorhombic in higher concentration of x > 0.000, x > 0.100 and x > 0.025 for the Eu, Dy and Yb samples, respectively. Consequently, the analyses showed a decrease of the lattice parameter c and volume fraction for the Bi-2223 phase with the substituted sample while the SEM investigations showed that the surface morphology of microstructures had degraded, the grain connectivity became weak and the porosity increased with RE concentration. This resulted in the degradation of superconducting properties and it exhibited less grain alignment and connectivity that resulted in the decline of Jʗ with RE substitution…